Pengelolaan Dana Tambang Tradisional Persfektif Maslahah-mursalah (Studi Kasus Tambang Batu Dan Pasir Di Desa Tanjung Kecamatan Ulu Barumun Kabupaten Padang Lawas) - Hakim Martua Lubis; Rahmad Efendi (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research highlights the importance of managing traditional stone and sand mining funds where stone and sand mining is an asset that must be managed and utilized properly for the welfare of the community. Stone and sand mineral resources are currently needed to support development, both the construction of roads, houses, buildings and so on, transparency and accountability in the management of stone and sand mineral natural resource funds are needed to bring benefit and eliminate harm. The purpose of this study is how the management of traditional stone and sand mining funds in Tanjung Village, Ulu Barumun District, Padang Lawas Regency and how the management of traditional stone and sand mining funds is viewed from the perspective of Maslahah-mursalah. This research is Empirical Juridical research with a qualitative approach. The results of the study prove that the management of traditional stone and sand mining funds is not in accordance with the principles of justice, transparency and accountability to ensure that this traditional mining activity brings benefits and avoids harm to the community in this case the harm that arises is more than the benefit due to the management of funds that have not run according to what was agreed upon, in order to create a sense of justice and prevent misuse of traditional stone and sand mining funds, transparency is needed to ensure that traditional mining is managed in accordance with the objectives that have been deliberated and agreed upon together.